Corticosteroids, Plasmapheresis, Argatroban, Rituximab, and Sirolimus Provided Clinical Benefit for Catastrophic Antiphospholipid Syndrome in a Patient with a History of Heparin-Induced Thrombocytopenia - Hasan, Haytham; Surjancev, Ivana; Arnason, Jon A.; Garg, Shivani; Rose, William Nicholas (Case Reports in Rheumatology, 2023)
We report a patient with catastrophic antiphospholipid syndrome who had significant improvement after corticosteroids, plasmapheresis, argatroban, rituximab, and sirolimus. Argatroban was used instead of heparin due to a history of heparin-induced thrombocytopenia.